The Knot Itself: Tangling with Multiculturalism - Boon, Sonja; Connolly, Deirdre (Journal of the Canadian Association for Curriculum Studies, 2022)
Multiculturalism has defined Canadian identity, both within and beyond its borders, for fifty years. Supporters laud the policy’s celebration of unity through difference. Critics, meanwhile, argue that this celebration is superficial. Canada’s multiculturalism policy, they say, obscures the workings of power in processes entrenching structural inequalities. Taking a reflexive approach, we—a mixed-race settler immigrant who arrived in Canada as a young child in 1975, and a White settler Canadian born in Halifax in the 1990s—interrogate our experiences and understandings of multiculturalism. Using collaborative autoethnography and found poetry, we examine our affective encounters and engagements with settler multiculturalism. In the process, we tangle with questions of (non)arrival, belonging, migration, branding and identities. Ultimately, we suggest that thinking through the knot and knottiness of multiculturalism can offer a path towards more nuanced and complicated futures.